Communicative Informatics: An Active and Creative Audience Framework of Social Media - Linda M. Gallant; Gloria M. Boone (tripleC: Communication, Capitalism & Critique)
Communicative informatics reflects the interactive complexity of web-based communication and a paradigm shift away from mass communication. Three discursive spheres (database and information systems, human computer interaction, and active audiences) work together to control online communication openness and its consequences for post-mass media society’s public common. This has implications for communication freedom, creativity, and constraints in an information-based society. Four propositions shed light on how online audience activity is encouraged by and imperative to corporate interests; how audience creativity can create, accept, or reject messages; how the online audience is monitored; and how online rhetoric can produce or inhibit public commons. Evidence shows that social media’s corporate interests can be at odds with online privacy and citizen communication. This tension is explored with a unique focus on rhetoric, argument, and the communication between audience members and Internet-based corporate media by way of digitized communication feedback loops.